Placing Industry in the Frame: Exploring the Mediated Performance of Industry Voices in Climate Change Reporting - Matthews, Julian (Frontiers in Communication, 2018)
It is now recognised that industry representatives influence the news reporting of climate change. Still, debate continues over the form and the extent of their influence particularly in the absence of detailed analysis of their presence across time. This paper places industry in the frame by analysing their perspectives within a period of rapid politicization of the issue in the UK (2000-2010). Mapped across elite reporting, industry presence appears to be fluid, not static, and to respond to the politicization of the issue and to the journalistic logic that shapes elite coverage. Perhaps as expected, industry is pro-active in providing a perspective on climate change as an economic problem and projecting its ‘green credentials’ in prime positions across the reporting. Mostly, however, this reporting uses its reactions to comment on other industry or elite activities, practices and policy. The findings show that interactions between the media and the political context underpin the observed outcomes of the pro-active and the re-active public relations by industry, in addition to shaping the presence of other speakers that contribute to the complex issue of climate change.